Dairy farming production factors in Garut and Bogor - Muljadi, Agus; Saleh, Achmad (Indonesian Animal Sciences Society, 1995)
Dairy farming in West Java is still dominated by small scale. The research focussed on production factors of dairy fanning which are influencing the farmers income from selling milk . The research was carried out in 1993 via survey to 30 respondents in Garut and Bogor. The results showed that the profit earned per month from dairy farming was Rp 130,331 and Rp 118,449 in Garut and Bogor, respectively . Return to labor from dairy farming was Rp. 4.56 in Bogor and Rp. 4.38 in Garut. The production factors positively affecting the income of the farmers from selling milk were cost for barn, concentrate feed, animal health care and artificial insemination, labor, and number of lactating cows . In addition, several production factors such as cost for forages, retribution cost, and number of male calf were proven negatively affecting the income of the Canners from selling milk . Therefore, thrive related production factors should be considered in developing small scale dairy farming, not only from availability of inputs but also from institutional aspect . Key words : Production factor, milk, dairy cows